The Political Economy of Resale Price Maintenance - Marvel, Howard P.; McCafferty, Stephen (Journal of Political Economy, 1986)
Although many economists argue that resale price maintenance (RPM) enhances the efficiency of distribution systems, RPM has proven politically unpalatable. Opposition to RPM arises primarily from concern that it raises prices, an empirical judgment based on comparisons of prices in RPM states with prices in "free-trade" (non-RPM) jurisdictions. We develop a model of RPM pricing that shows that prices chosen by manufacturers under universal RPM are close to those chosen without RPM. Manufacturers "pay" for dealer services through lowered wholesale prices. When jurisdictions are mixed, manufacturers select compromise wholesale prices, and retail prices in RPM jurisdictions exceed those in free-trade states. We use the theoretical results as a basis for the analysis of the evolution of political attitudes toward RPM.